Comparative effects of parsley leaves aqueous extract and ramipril on gentamicin induced nephrotoxicity in rats - Eisha Akram; Akbar Waheed; Rukhsana Munawar; Sidra Mumal; Abdul Azeem (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Rats are commonly used in experimental studies as they have a smaller body size, they are easily available, and their genetic profiles are similar to each other as compared to humans. Kidney pathologies are the result of an imbalance between reactive oxygen species and antioxidants. Parsley aqueous extract is rich in polyphenolic contents and has nephroprotective effects. The objective of this study is to observe the effects of ramipril and parsley leaves aqueous extract in gentamicin induced nephrotoxicity. METHODOLOGY: An Experimental study consisting of 40 healthy male albino rats were randomly distributed into two categories after taking samples for baseline values of urea and creatinine: Category 1 consisted of a control group (Group 1) having 10 rats, while category 2 comprised of 30 rats, divided into three experimental groups after being given intraperitoneal injections of gentamicin (80mg/kg) per day. Group 2 was taken as disease control, while group 3 and group 4 were parsley treated and ramipril treated for 28 days, respectively. Biochemical markers (serum urea and creatinine) were done at day 35. SPSS version 22 was applied for Statistical analysis. One-way ANOVA test was used to determine any difference in mean values. Post hoc tuckeys test was applied for multiple comparisons amongst groups. p<0.05 was measured as significant. RESULTS: The treatment decreased the levels of serum urea and creatinine in nephrotoxic rats in group 3 (parsley treated group) and group 4 (ramipril treated group) in comparison to group 2. Group 3 had significantly reduced biochemical markers (p<0.05). CONCLUSION: Parsley leaves extract significantly reduced the serum urea and creatinine levels as compared to ramipril.